## Precalculus (6th Edition) Blitzer

The required values are $f\left( g\left( x \right) \right)=x$ and $g\left( f\left( x \right) \right)=x$. The functions $f\left( x \right)=4x$and $g\left( x \right)=\frac{x}{4}$ are inverses of each other.
Consider the functions: $f\left( x \right)=4x$ and $g\left( x \right)=\frac{x}{4}$ The equation for $f$ is given as: $f\left( x \right)=4x$ Replace $x$ with $g\left( x \right)$ \begin{align} & f\left( g\left( x \right) \right)=4g\left( x \right) \\ & =4\left( \frac{x}{4} \right) \\ & =x \end{align} Now, to find $g\left( f\left( x \right) \right)$ Consider the function $g\left( x \right)$: $g\left( x \right)=\frac{x}{4}$ Replace $x$ with $f\left( x \right)$ \begin{align} & g\left( f\left( x \right) \right)=\frac{f\left( x \right)}{4} \\ & =\frac{\left( 4x \right)}{4} \\ & =x \end{align} Because $g$ is the inverse of $f$ (and vice-versa), the inverse notation can be used: $f\left( x \right)=4x$ and $\text{ }{{f}^{-1}}\left( x \right)=\frac{x}{4}$ It can be easily observed that ${{f}^{-1}}$ can be expressed in $f$ if multiplied by 4. \begin{align} & \text{ }{{f}^{-1}}\left( x \right)=\frac{x}{4} \\ & =g\left( x \right) \end{align} Hence, the values are $f\left( g\left( x \right) \right)=x$ and $g\left( f\left( x \right) \right)=x$, the functions $f\left( x \right)$ and $g\left( x \right)$are inverse of each other.